Memory and Enlightenment Cultural Afterlives of the Long Eighteenth Century - Ward, James (Palgrave Macmillan Memory Studies, 2018)
This book illuminates how the 'long eighteenth century' (1660-1800) persists in our present through screen and performance media, writing and visual art. Tracing the afterlives of the period from the 1980s to the present, it argues that these emerging and changing forms stage the period as a point of origin for the grounding of individual identity in personal memory, and as a site of foundational traumas that shape cultural memory. .